Predicting Corporate Financial Distress Using Logit Model: The Case of Malaysia - Soo-wah Low; Fauzias Mat Nor; Cik Puan Yatim (Asian Academy of Management Journal, 2001)
The study examines the usefulness of financial ratios in prediciting the probability of financial distress in companies. These financially troubled companies have obtained court protection against their creditors under Section 176 of the Malaysian Companies Act, 1965. The findings suggest that the fairly popular ratios of liquidity and profitability maybe somewhat deceiving. Interpretation of these two measured should be made carefully because high ratios by themselves do not necessarily imply that the company has sufficient money to pay its obligations. It is shown that the cash position of a company provides a better warning signal of financial deterioration and therefore should be emphasized in detecting financially distressed companies. The predictive ability of the model is tested on a holdout sample and the overall accuracy rate for the estimation and the holdout samples are 82.4% and 90% respectively. The findings provide a better understanding on the relevant factors that lead to corporate distress so that prompt actions could be taken to minimize the risk of financial distress.